Model Integratif Digitalisasi Sastra Lisan Madura dalam Pembelajaran Bahasa Indonesia: Pendekatan Literasi Budaya di Era Digital - Moh. Badrih (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study stems from the limited research integrating Madurese oral literature into Indonesian language learning. Its utilization in formal education remains low due to the lack of appropriate teaching materials and learning models aligned with the digital era. This research aims to develop and examine the effectiveness of an integrative learning model based on the digitalization of Madurese oral literature to enhance students’ cultural literacy. The study employed a Research and Development (R&D) design adapting Borg and Gall’s model, which consists of six stages: preliminary study, model design, product development, limited trial, revision, and field testing. The participants were 120 high school students selected through purposive sampling based on digital readiness and institutional support for culturally based innovation. Data were collected through questionnaires, observations, interviews, and cultural literacy tests, using instruments validated by three experts in Indonesian language education, Madurese culture, and digital media. Quantitative data were analyzed using a paired-sample t-test, while qualitative data were analyzed thematically. The results showed a significant improvement in cultural literacy scores, from 52.5 to 85.25 (p < 0.05), representing a 32.75% increase. These findings confirm that the integrative digitalization model of Madurese oral literature is effective for upper secondary education as a contextual pedagogical strategy to strengthen cultural literacy in the digital era.